A survey on decision-making based on system reliability in the context of Industry 4.0. (July 2020) - Hoffmann Souza, Marcos Leandro; da Costa, Cristiano André; de Oliveira Ramos, Gabriel; da Rosa Righi, Rodrigo
Highlights: Analyzes state of the art in reliability for decision-making regarding Industry 4.0. Proposes a taxonomy of decision making focusing reliability, with challenges/goals. Presents decision types in terms of decision levels, local, vertical, and horizontal. The methodology consisted of a systematic review of the literature in the area. Reliability is not considered to optimize the business in horizontal decisions. Abstract: The business world is continually changing. Dynamic environments, full of uncertainties, complexities, and ambiguities, demand faster and more confident decisions. To compete in this environment, Industry 4.0 emerges as an essential alternative. In this context, the reliability of manufacturing is an essential aspect for companies to make successful decisions. In the literature, several technologies associated with Industry 4.0 have been applied to improve the availability of equipment, including the Internet of Things (IoT), Cyber-Physical Systems (CPS), blockchain, and data mining. Nevertheless, there is still no survey study that seeks to show how reliability has collaborated to support decision-making in organizations, in the context of Industry 4.0. In general, most applications still focus on the productivity and health of individual equipment. However, in today's volatile and complex businesses, local decisions are no longer sufficient; it is necessary to analyze the organization entirely. Thus, being aware of the impacts that a local failure can impose on the entire company has significant weight in the decision-making process. In this context, this article presents a survey to identify how researches on systems reliability has contributed to and supported the development of decision-making in Industry 4.0. The main contribution of this article is to highlight how reliability can be used to support different types of strategic decisions in the context of Industry 4.0. Finally, it highlights the need for research associating management decisions with the technologies of Industry 4.0.